OPERATIONAL STRATEGIES AND ENHANCEMENT OF MATERNAL AND CHILD HEALTHCARE SERVICE DELIVERY IN DEVOLVED HEALTHCARE UNITS IN MACHAKOS COUNTY - Kavindu, Therecia Mwende; Wamitu, Dr. Susan Njeri (European Journal of Business and Strategic Management, 2019)
Purpose: Operational strategies are very critical if an organization is to achieve its objectives. By developing them, organizations could examine and implement effective and efficient systems for using resources, personnel and the work process. This study was geared towards establishing Operational Strategies and Enhancement of Maternal and Child Healthcare Service Delivery in Devolved Healthcare Units in Machakos County. Methodology: This study adopted a descriptive research design and the study targeted 600 employees working in Machakos County Referral and Sub county hospitals. Two sampling techniques were used; purposive sampling on the county referral hospital and simple random sampling on the sub county hospitals where the sample size was obtained by calculating 30% of the target population to obtain 180 respondents. Data collection was carried out through administration of questionnaires. Data was analyzed using descriptive and inferential statistics using the Statistical Package for Social Sciences (SPSS) version 24.0 and findings tabulated and presented in form of tables. Findings: Descriptive statistics and regression analysis indicated that there was a positive relationship between operational strategies and enhancement of MCH services in devolved healthcare units. The findings of this study were in tandem with those of the previous studies reviewed. The study concluded that operational strategies influence enhancement of MCH service delivery in devolved healthcare units in Machakos County. Unique Contribution to Policy, Practice and Academia: The study recommended that the health administrators and other stakeholders should adopt operational strategies that enhance MCH service delivery in health facilities across the county.